Effect of Resveratrol on Cultured Skin Fibroblasts from Patients with Oxidative Phosphorylation Defects. (26th April 2013) - De Paepe, Boel; Vandemeulebroecke, Katrien; Smet, Joél; Vanlander, Arnaud; Seneca, Sara; Lissens, Willy; Van Hove, Johan LK; Deschepper, Ellen; Briones, Paz; Van Coster, Rudy
<x xml:space="preserve">Abstract</x> Few therapeutic options are available to patients with oxidative phosphorylation disorders. Administering pharmacological agents that are able to stimulate mitochondrial biogenesis have been put forward as a possible treatment, yet the approach remains in need of thorough testing. We investigated the effect of resveratrol in an in vitro setting. Mitochondrial enzymatic activities were tested in cultured skin fibroblasts from patients harboring a nuclear defect in either complex II or complex IV (n = 11), and in fibroblasts from healthy controls (n = 11). In the latter, preincubation with resveratrol resulted in a significant increase of citrate synthase, complex II and complex IV enzyme activity. In patients with complex II or complex IV deficiency, however, activity of the deficient complex could not be substantially augmented, and response was dependent upon the residual activity. We conclude that resveratrol is not capable of normalizing oxidative phosphorylation activities in deficient cell lines. Copyright © 2013 John Wiley & Sons, Ltd.